Novel BMP4 Truncations Resulted in Opposite Ocular Anomalies: Pathologic Myopia Rather Than Microphthalmia - Jiang, Yi; Ouyang, Jiamin; Li, Xueqing; Wang, Yingwei; Zhou, Lin; Li, Shiqiang; Jia, Xiaoyun; Xiao, Xueshan; Sun, Wenmin; Wang, Panfeng; Zhang, Qingjiong (Frontiers in Cell and Developmental Biology, 2021)
BMP4 variants has been reported to be associated with syndromic microphthalmia (MCOPS6, OMIM 607932). This study aims to describe BMP4 truncation mutations contributing to a novel phenotype in eight patients from four Chinese families. In this study, BMP4 variants were collected from a large dataset from in-house exome sequencing. Candidate variants were filtered by multiple in silico tools as well as comparison with data from multiple databases. Potential pathogenic variants were further confirmed by Sanger sequencing and cosegregation analysis. Four novel truncation variants in BMP4 were detected in four out of 7314 unrelated probands with different eye conditions. These four mutations in the four families solely cosegregated in all eight patients with a specific form of pathologic myopia, characterized by significantly extended axial length, posterior staphyloma, macula patchy, chorioretinal atrophy, myopic optic neuropathy or glaucoma, vitreous opacity, and unique peripheral snow-grain retinopathy. The extreme rarity of the truncations in BMP4 (classified as intolerant in the gnomAD database, pLI = 0.96), the exclusive presence of these variants in the four families with pathologic myopia, variants fully co-segregated with the same specific phenotypes in eight patients from the four families, and the association of the pathogenicity of truncations with syndromic microphthalmia in previous studies, all support a novel association of BMP4 truncations with a specific form of pathologic myopia. The data presented in this study demonstrated that heterozygous BMP4 truncations contributed to a novel phenotype: pathologic myopia rather than microphthalmia. Mutations in the same gene resulting in both high myopia and microphthalmia have been observed for a few other genes like FZD5 and PAX6, suggesting bidirectional roles of these genes in early ocular development. Further studies are expected to elucidate the molecular mechanism of the bidirectional regulation.